Postpartum Discharge on Labetalol was Associated with Increase Risk of Readmission for Hypertension Compared with Discharge on Nifedipine - Nayla Salman, Amara Mumtaz, Sobia Noreen, Anoos Butt, Madiha Ahmed, Touseef Fatima, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Hypertension complicating pregnancy is common and, when uncontrolled, can have devastating consequences. Objectives: The main objective of the study is to find the postpartum discharge on labetalol was associated with increase risk of readmission for hypertension compared with discharge on nifedipine. Material and methods: This cross-sectional study was conducted in Islam medical college and teaching hospital Sialkot during June 2022 to September 2022. The data was collected with the permission of ethical committee of hospital. Data was collected with the permission of ethical committee of hospital. Participants were randomized to labetalol versus extended release nifedipine using a computerized random number generator. Results: Data was collected from 50 female patients. Baseline maternal characteristics were similar between groups, including age, race, body mass index (BMI), gravidity and parity, rate of twins, and presence of medical comorbidities including chronic hypertension. Data was collected in two groups, one group of labetalol and second group of nifedipine. Practical implication: This study will help us to find the efficacy of both the drugs that we used in the study for the purpose of postpartum hypertension. Conclusion: It is concluded that both oral labetalol and oral extended release nifedipine are effective and well tolerated for management of postpartum hypertension. Keywords: Hypertension, Postpartum, Oral, Management, Labetalol, Nifedipine